PELAKSANAAN KEGIATAN MBKM KEWIRAUSAHAAN TERHADAP USAHA PAW PARTY - Aryon, Debora Christina; Utama, Louis; Sutantio, Angelia; Wilbert, Davin; Cynthia, Emelia; Cristian, Steven (Jurnal Serina Abdimas, 2024)
The implementation of MBKM Entrepreneurship activities is a highlight in efforts to develop entrepreneurial skills among students. This study reveals the implementation of MBKM Entrepreneurship in the context of the "Paw Party" business, which focuses on the production and sale of special cakes for dogs. Through the concept of "Freedom to Learn" and the support of supervisors, the Paw Party team developed a business plan and carried out its operations, including promotions, online sales and participation in bazaars. By using the Lean Model Canvas, Paw Party succeeded in finding market opportunities and presenting unique and quality products. Many anabul owners are looking for snacks and food that are useful, healthy and taste good. This is not yet widely found on the pet food market because many of the others do not consider the composition and beneficial ingredients. Now Paw Party is here to provide snacks that are not only liked by the little ones but contain omega-3 which helps the little ones' fur growth. Apart from that, Paw Party snacks are made from pumpkin and sweet potatoes as a source of fiber, and contain vitamins A, C and E. The author also innovates by presenting new snack variants made from meat to answer the needs of children. Then, Paw Party presents snacks that are reliable in quality because they have lots of reviews from both customers and influencers. The results show that MBKM Entrepreneurship activities not only provide practical experience to students, but also open up opportunities for sustainable business development. Through this effort, it is hoped that it can encourage the growth of creative and innovative young entrepreneurs in Indonesia. ABSTRAK Pelaksanaan kegiatan MBKM Kewirausahaan menjadi sorotan dalam upaya pengembangan keterampilan kewirausahaan di kalangan mahasiswa. Studi ini mengungkapkan implementasi MBKM Kewirausahaan dalam konteks bisnis "Paw Party", yang berfokus pada produksi dan penjualan kue-kue khusus untuk anjing. Melalui konsep "Merdeka Belajar" dan dukungan dosen pembimbing, tim Paw Party mengembangkan rencana bisnis dan menjalankan operasionalnya, termasuk promosi, penjualan online, dan partisipasi dalam bazaar. Dengan menggunakan Lean Model Canvas, Paw Party berhasil menemukan peluang pasar dan menghadirkan produk yang unik dan berkualitas. Banyak dari pemilik anabul mencari cemilan dan makanan yang bermanfaat, sehat, dan rasanya enak. Hal ini belum banyak ditemukan di pasaran makanan hewan karena banyak dari yang lain kurang mempertimbangkan komposisi dan bahan yang bermanfaat. Kini Paw Party hadir untuk memberikan cemilan yang tidak hanya disukai oleh anabul tetapi memiliki kandungan omega-3 yang membantu untuk pertumbuhan bulu anabul. Selain itu, cemilan Paw Party berbahan dasar labu dan ubi sebagai sumber serat, lalu mengandung vitamin A,C, dan E. Penulis juga berinovasi dengan menghadirkan varian cemilan baru berbahan daging untuk menjawab kebutuhan anabul. Lalu, Paw Party menghadirkan cemilan yang terpercaya kualitasnya karena sudah memiliki banyak review baik dari pelanggan maupun influencer. Hasil menunjukkan bahwa kegiatan MBKM Kewirausahaan tidak hanya memberikan pengalaman praktis kepada mahasiswa, tetapi juga membuka peluang bagi pengembangan bisnis yang berkelanjutan. Melalui upaya ini, diharapkan dapat mendorong pertumbuhan wirausaha muda yang kreatif dan inovatif di Indonesia